Prolapsed anorectal malignant melanoma presenting as hemorrhoids. Issue 1 (2nd January 2023) - Songtanin, Busara; Nugent, Kenneth; Islam, Sameer
Abstract: Rectal bleeding in a patient with a history of hemorrhoids should not be ignored. It is often benign and resolves spontaneously without treatment. Here we present a case of anorectal malignant melanoma that presented with rectal bleeding and a prolapsed rectal mass.